TAT as a new marker and its use for noninvasive chemical biopsy in NASH diagnosis - Sihyang Jo; Jin-Mo Kim; Minshu Li; Han Sun Kim; Yong Jin An; Sunghyouk Park (Molecular Medicine)
Abstract Background Early diagnosis of Nonalcoholic steatohepatitis (NASH) is crucial to prevent its progression to hepatocellular carcinoma, but its gold standard diagnosis still requires invasive biopsy. Here, a new marker-based noninvasive chemical biopsy approach is introduced that uses urine-secreted tyrosine metabolites. Methods We first identified NASH-specific decrease in TAT expression, the first enzyme in the tyrosine degradation pathway (TDP), by employing exometabolome-transcriptome correlations, single-cell RNA -seq, and tissue staining on human NASH patient samples. A selective extrahepatic monitoring of the TAT activity was established by the chemical biopsy exploiting the enzyme’s metabolic conversion of D2-tyrosine into D2-4HPP. The approach was applied to a NASH mouse model using the methionine-choline deficient diet, where urine D2-4HPP level was measured with a specific LC-MS detection, following oral administration of D2-tyrosine. Results The noninvasive urine chemical biopsy approach could effectively differentiate NASH from normal mice (normal = 14, NASH = 15, p = 0.0054), correlated with the NASH pathology and TAT level decrease observed with immunostaining on the liver tissue. In addition, we showed that the diagnostic differentiation could be enhanced by measuring the downstream metabolites of TDP. The specificity of the TAT and the related TDP enzymes in NASH were also addressed in other settings employing high fat high fructose mouse NASH model and human obesity vs. NASH cohort. Conclusions Overall, we propose TAT and TDP as pathology-relevant markers for NASH and present the urine chemical biopsy as a noninvasive modality to evaluate the NASH-specific changes in urine that may help the NASH diagnosis.